Determinación de las propiedades funcionales y fisicoquímicas de aislado proteico liofilizado extraído por solubilización y precipitación isoeléctrica a partir de bazo de vacuno - Hinostroza Guanilo, Andy Ernest Mathiuk (2023)
The objective of the research was to determine the functional and physicochemical properties of the protein isolate. The solubilization and isoelectric precipitation method was used, being the raw material male bovine spleens obtained from the Salaverry slaughterhouse. The bovine spleen was homogenized with distilled water at 4°C in a ratio of 1/9, solubilized at pH 12.5 with 5N NaOH and then centrifuged at 10,500 rpm for 20 minutes. The supernatant was precipitated at pH 5.5 with 2N HCl, then subjected to centrifugation, the sediment was dried by lyophilization and subsequently ground. The physicochemical properties of the powdered protein isolate were determined, obtaining as results in the final product a humidity of 6.45%, protein 80.8%, fat 4.49%, ash 2.15% and carbohydrates 2.24%, pH of 6.03 and an acidity expressed in % of 0.73% lactic acid. Likewise, the functional properties were determined, obtaining a Solubility of 86.3%, CRA 2.53 ml of water/g of protein, CLG 2.13 ml of oil/g of protein, CE 1023.33 ml of oil/g of protein, CFE 1.29 ml of volume gained. , EEC 90.96% stability, 115 mg/kg. Concluding that the protein isolate from bovine spleen has excellent physicochemical and functional properties, this allows us to affirm that it could be used in the food industry (sausages, minced meats), bakery pasta, soups, sauces, sports drinks, confectionery, pastry, ice cream and as an emulsifying agent for dressings) and pharmaceutical. Further research is needed to evaluate its sensory characteristics, commercial viability, and potential applications.